Iron deficiency in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention. (1st February 2020) - Cosentino, Nicola; Campodonico, Jeness; Pontone, Gianluca; Guglielmo, Marco; Trinei, Mirella; Sandri, Maria Teresa; Riggio, Daniela; Baggiano, Andrea; Milazzo, Valentina; Moltrasio, Marco; Muscogiuri, Giuseppe; Bonomi, Alice; et al.
Abstract: Background: Iron deficiency (ID) is a known co-morbidity and a potential therapeutic target in heart failure. Whether ID is frequent also in ST-segment elevation acute myocardial infarction (STEMI) patients and is associated with worse in-hospital outcomes has never been evaluated. Methods: We defined ID as a serum ferritin < 100 μg/L or transferrin saturation < 20% at hospital admission. We assessed the association between ID and the primary endpoint (a composite of in-hospital mortality and Killip class ≥ 3). We explored the potential association between ID, circulating cell-free mitochondrial DNA (mtDNA), and cardiac magnetic resonance (CMR) parameters. Results: Four-hundred-twenty STEMI patients undergoing primary percutaneous coronary intervention (pPCI) were included. Of them, 237 (56%) had ID. They had significantly higher admission high-sensitivity troponin and mtDNA levels as compared to non-ID patients (145 ± 35 vs. 231 ± 66 ng/L, P < 0.001; 917 [404–1748] vs. 1368 [908–4260] copies/μL; P < 0.003, respectively). A lower incidence of the primary endpoint (10% vs. 18%, P = 0.01) was observed in ID patients (adjusted OR 0.50 [95% CI 0.27–0.93]; P = 0.02). At CMR (n = 192), ID patients had a similar infarct size (21 ± 18 vs. 21 ± 19 g; P = 0.95), but a higher myocardial salvage index (0.56 ± 0.30 vs. 0.43 ± 0.27; P = 0.002), and a smaller microvascular obstruction extent (3.6 ± 2.2 vs. 6.9 ± 3.9 g; P < 0.001). Conclusions: Iron deficiency is frequent in STEMI patients, it is coupled with mitochondrial injury, and, paradoxically, with a better in-hospital outcome. This unexpected clinical result seems to be associated with a smaller myocardial reperfusion injury. The mechanisms underlying our findings and their potential clinical implications warrant further investigation. Highlights: Iron deficiency (ID) is a frequent condition in patients with STEMI. It is associated with mitochondrial injury, as reflected by higher levels of mitochondrial DNA. ID is paradoxically associated with a better in-hospital outcome. This result is associated with a lower myocardial reperfusion injury, as assessed by CMR.